Eu weaknesses and the debate about its future reforms - B. Valchev (Trakia Journal of Sciences)
The paper examines the deep causes of the crisis the European Union is going through. The main argument is that the current decision-making mechanism of the EU dominated by the member states is unsustainable and needs to be revised. The ability of member states to block decisions in the crucial EU institutions – the European Council and Council – is a major weakness which makes the decision-making process extremely slow and ineffective during crises and external pressures. Three different alternatives for reforms of the EU decision-making are presented which include a transition towards a parliamentarian or a presidential system. These alternatives are evaluated according to their potential to overcome the weaknesses the current system is suffering. The main weakness of a parliamentary system at EU level consists in the risk of instability of the Commission due to the fragmentation in the European parliament. The adoption of a presidential system with a directly elected European President might solve most of the present problems of the EU. This solution however lacks the support of the member states who will take the final decision and only a strong public support may increase the chances for such reforms